The 'Glass of Milk' Subsidy Program and Malnutrition in Peru - Stifel, David; Alderman, Harold (Oxford University Press on behalf of the World Bank, 2013)
This study of the Vaso de Leche ('glass of milk') feeding program in Peru looks for evidence that this in-kind transfer program aimed at young children furthers nutritional objectives. The study links public expenditure data with household survey data to substantiate the targeting and to model the determinants of nutritional outcomes. It confirms that the social transfer program targets poor households and households with low nutritional status. Nevertheless, the study fails to find econometric evidence that the nutritional objectives are being achieved.